Traveler’s recommendation mobile based system around Terengganu / Muhammad Aiman Syakir Shamsudin - Shamsudin, Muhammad Aiman Syakir (2021)
Currently, Recommender Systems are used in several different areas. Main purpose of this project is the application of a recommendation system in tourism. As people visit new places, a new culture, new climate, new people and new sceneiy are encountered. For travel planning tourists usually look for location information, such as reviews, route from source to destination, time of departure, time of end, address, accommodations and nearby attractions. Tourists may sometimes consult travel companies to plan their trip. Tourists have to plan their trip according to the agencies available packages. When travel agencies plan a journey, the tourist's interest and requirements are not taken into account. Even if tourists are not interested, people in agencies persuade tourists to package themselves. Generalized packages are offered by tourist organizations and give tourists no freedom of choice for their hotels and restaurants. To solve this project proposes a mobile application system to give the recommendations about the best location to the user based on the user's current location, interest and need. This system also provides information, images and reviews about that recommendation location so that it will help users to decide where to visit. To target more people to use this app, this application be created in an android based application for early prototype. This android based application is created by using the Java programming language.